Collaboration and co-creation new platforms for marketing and innovation - Bhalla, Gaurav; SpringerLink (Online service). (New York Springer, 2011)
Praise for Collaboration and Co-Creation "In today's customer-empowered world, collaboration and co-creation competencies are critical to the future growth of a company.Gaurav Bhalla offers a concrete framework and specific examples that managers can use to implement value co-creation programs with their customers. A must-read for companies not wishing to get left behind! --Vijay Govindarajan, Earl C. Daum 1924 Professor of International Business, Tuck School of Business, Dartmouth College Collaboration and co-creation is the sweet spot for rethinking how companies should practice marketing and innovation Gaurav Bhalla's book is very timely, and offers readers an effective way for building businesses around customers. --Nicolas Mirzayantz, Group President, Fragrances, International Flavors and Fragrances Companies can't afford to fake it. Customer-driven innovation has moved from the edge to become a core business practice. Gaurav Bhalla helps you understand what it takes to make this shift, and not a moment too soon. --John Hagel III, Co-Chairman, Deloitte Center for the Edge, and co-author, The Power of Pull If running your business seems more difficult lately, reading this book will help you understand why. It will also provide insights into how collaboration and co-creation can improve your company's performance. --Vince Barabba, Author, Meeting of the Minds, and Founder and Chairman, Market Insight Corporation Gaurav Bhalla is after big game: how the world's leading institutions are connecting and collaborating with their most important asset their customers in novel and important ways. This book is an important one to read for any marketing, market research, or product innovation professional. --Steve Howe, CEO, Passenger ?Based on my research it is clear that user co-creation is a strong driver for transforming the marketing and innovation programs of those companies that dare to listen and respond. Gaurav Bhalla provides a solid framework to guide this process and a rich set of case stories to explain why and how.? --Jacob Buur, Professor of Participatory Innovation, Research Director of SPIRE, University of Southern Denmark.
Collaboration and Co-creation -- A Framework for Implementation -- Listen -- Engage -- Respond Externally: Co-creation -- Respond Internally: Organizational Alignment -- Rethinking Marketing and Innovation -- Beyond the Business World
Electronic reproduction.
Keywords: Marketing; Electronic books